PERBANDINGAN EFEKTIVITAS ANTARA MINYAK CENGKEH (Syzigium aromaticum) DAN LARUTAN OBAT KUMUR YANG MENGANDUNG DAUN SIRIH DALAM MENGHAMBAT PERTUMBUHAN MIKROORGANISME PEMBENTUK PLAK GIGI SECARA IN VITRO - Bahar, Meiskha; Sudomo, Pertiwi (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2015)
Dental plaque is formed by colony of bacteria attached to the tooth’s smooth surface. Plaque on the tooth caused by the type of food consumed and the activity of thousands of microorganisms. The main microorganisms that forming dental plaque is Streptococcus mutans. If plaque is not removed daily by brushing it will become a hard tartar. Dental plaque can be removed by brushing or flossing between teeth or use mouthwash solution containing antimicrobial agents. One of the types of plant that has the ability to inhibit and kill the microorganisms is clover (Syzigium aromaticum). The aim of this study is to determine the effectiveness of bioactive compounds contained in clove oil isolated microorganisms from dental plaque and the compared with the mouthwash solution containing betel leaf in inhibiting the growth of the bacteria. This study was an experimental research approach post test only control group design with 40 isolates of dental plaque bacteria samples which were selected to find out the type of S.mutans. The result showed that clove oil concentration of 10%; 20%; 30%; dan 40%, have the ability to inhibit S. mutans as well as the other 39 isolates of dental plaque dental bacteria. Based on the analysis of data from the one-way ANOVA test showed significance of 0.05 which means there was no significant difference in the inhibition of clove oil againts dental plaque bacteria isolates of S. mutans and the other 30 isolates of dental plaque in various concentrations.